The Impact Of Insufficient Sleep On Body Health - Teleayo, Anuoluwaop (PSPP JOURNALS, 2023)
Insufficient sleep poses a big public health challenge, exerting profound results on physical health, cognitive feature, emotional well-being, and social properly-being. This qualitative study aimed to discover the perceptions of insufficient sleep, its impact on body health, coping mechanisms, and implications for intervention and public health. Through semi-based interviews and thematic analysis, facts had been accumulated from a purposive pattern of 20 contributors recruited from diverse backgrounds. The findings revealed multifaceted perceptions of inadequate sleep, which includes frustration, resignation, and cultural affects on sleep norms. Insufficient sleep became related to heightened susceptibility to cardiovascular issues, metabolic dysregulation, and immune dysfunction. Participants reported cognitive impairments, temper disturbances, and challenges in interpersonal relationships. Coping mechanisms protected mindfulness practices, relaxation techniques, and adherence to sleep hygiene standards. Implications for intervention and public fitness underscored the importance of raising recognition, integrating sleep assessment into scientific exercise, addressing social determinants of sleep health, and fostering interdisciplinary collaborations. By prioritizing sleep health and enforcing proof-based interventions, stakeholders can mitigate the load of sleep-related disorders and sell ultimate well-being for individuals and communities.